Mapping the scholarly landscape: a bibliometric exploration of school head leadership competency - Ambon, Josephine; Alias, Bity Salwana; Mansor, Azlin Norhaini (Journal of Education and Learning (EduLearn), 2025)
This bibliometric study examines the trends and contributions in school head leadership competencies from 2015 to 2024, using data from Scopus and employing VOSviewer. The research aims to provide a comprehensive overview of the scholarly literature on leadership competencies in the range of a school head. The methodology involves a thorough bibliometric process, including the organization, coordination, and analysis of bibliographic data from peer-reviewed academic journals. The specific methods used to define the research area are mapping of important contributors and co-authorship patterns, document co-citation analysis, and keyword frequency analysis. Preliminary results indicate a peak in publications up to 2023, with a notable decline in 2024. The study highlights significant international collaborations, with the United States at the core of a global network involving countries like Canada, Australia, and Turkey. Keywords such as "transformational leadership," "equity," and "school climate" are prominent, reflecting a broad approach to exploring effective leadership. In conclusion, the field of school head leadership competencies is dynamic, driven by global collaboration and evolving educational challenges. The recent decline in publications signals a need for new research directions. Future studies should explore unexplored areas and integrate technological advancements to enhance school head leadership competencies effectively.